Modeling of microfluid droplet resonator based on whisper gallery mode - Dong, Bin (2009)
Whisper Gallery Modes were first observed by elastic light scattering from spherical dielectric particles in liquid resonators. Currently most of the optical ring/sphere resonator based on whisper gallery mode is fabricated by wafer fabrication technology, which is high in cost and cannot be achieved on-chip. The microfluidic droplet resonator is formed by micro-scale droplet in solution; light will be coupled into the droplet from waveguide via evanescent wave. Since the droplet is formed by surface tension, the surface will be quite smooth, so that whisper gallery modes can be formed near the surface of the droplet, which means the light will be transmitted by total internal refraction near the surface and get accumulated. The smooth surface will assure a high Q-factor by reducing the surface scattering loses. The microfluidic droplet resonator can be easily realized in chip made by PDMS, which is low in cost and easily manipulated. Microfluidic droplet resonator can be used for biosensing like protein detection by embodied in the droplet and for measurement of refractive index of droplet with high accuracy. The whisper gallery modes within the droplet will be investigated and simulated. Various size, refractive index and geometry of the droplet resonator will also be simulated to optimize the detection precision and guide the manufacturing of the droplet resonator on-chip.